2014
DOI: 10.1159/000360087
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Timing of Native Kidney Biopsy Complications

Abstract: Background: The appropriate observation period, rate and risk factors of complications after a percutaneous renal biopsy remain debated. Methods: We retrospectively studied native kidney biopsies performed in our institution between January 2007 and July 2011. Outpatients had either an 8- (67%) or a 24-hour (33%) observation period. Results: 312 biopsies were reviewed (287 patients), 51% of patients were female and the mean age was 54 ± 15 years. Half of these biopsies were performed in outpatients. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 20 publications
8
76
1
Order By: Relevance
“…Although the overall incidence of requiring a blood transfusion in this meta-analysis was 0.9% (95% confidence interval, 0.4% to 1.5%), transfusion rates as high as 5%-9% have been described in large single-center case series from major academic centers (7,12,(35)(36)(37). This may be because of some PRBs being performed by nephrology trainees and more high-risk patients undergoing PRBs at large academic centers.…”
Section: Bleedingmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the overall incidence of requiring a blood transfusion in this meta-analysis was 0.9% (95% confidence interval, 0.4% to 1.5%), transfusion rates as high as 5%-9% have been described in large single-center case series from major academic centers (7,12,(35)(36)(37). This may be because of some PRBs being performed by nephrology trainees and more high-risk patients undergoing PRBs at large academic centers.…”
Section: Bleedingmentioning
confidence: 80%
“…Whittier and Korbet (42) found that 67% of major complications (need for transfusion or invasive procedure, acute renal obstruction or failure, septicemia, or death) occurred during the first 8 hours of observation, with 91% detected by 24 hours and 9% detected after 24 hours. In a smaller retrospective series, Simard-Meilleur et al (36) found that 100% of complications in outpatients undergoing PRB occurred within 8 hours versus 72% of complications in inpatients and that 10% of inpatients had complications .24 hours after PRB. The most recent large biopsy series found that 91% of major complications occurred within 12 hours of PRB, with 7.4% occurring between 12 and 24 hours and 1.85% occurring after 24 hours (43).…”
Section: Timing Of Complicationsmentioning
confidence: 96%
“…In the outpatient setting, it is important to know the timing of complications to determine the optimal post-biopsy observation period. In a study form France [18], 100% of complications occurred in outpatients within 8 h vs. 72% complications in inpatients, and 10% of inpatients had complications >24 h after biopsy. Historical data, prior to real-time US guidance, recommended longer observation periods [19].…”
Section: Introductionmentioning
confidence: 97%
“…Another large retrospective study conducted in Norway identified low platelet as the most important single risk factor in predicting post-procedural bleeding. Interestingly, lower bleeding risk was reported to be associated with outpatient procedure [9]. So far, rare research has focused on the structural effect of the biopsied kidneys on the bleeding risk.…”
Section: Introductionmentioning
confidence: 99%